Pengaruh Persepsi Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Nizam Ulul Azmy; Yustina Chrismardani (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to determine the influence of price perceptions and service quality on customer satisfaction at Bintang Sangak Cafe. This study uses a quantitative approach. In this research there are 2 independent variables, namely: Price Perception (X1), Service Quality (X2), and there is 1 dependent variable, namely Customer Satisfaction (Y). The number of samples studied in this research was 50 respondents. The data collection technique uses a questionnaire that has been tested for validity, reliability test, classical assumption test, multiple linear analysis test, hypothesis test (simultaneous F test, and partial T test). The results of the research show that the price variable, Service Quality variable and Facility variables influence Customer Satisfaction. And the data analysis method uses the SPSS 22 software application. The research results show that the Price Perception variable and the Service Quality variable influence Customer Satisfaction.